Photo-affinity labeling (PAL) in chemical proteomics: a handy tool to investigate protein-protein interactions (PPIs) - Murale, Dhiraj P.; Hong, Seong Cheol; Haque, Md. Mamunul; Lee, Jun-Seok (BIOMED CENTRAL LTD, 2017)
Protein-protein interactions (PPIs) trigger a wide range of biological signaling pathways that are crucial for biomedical research and drug discovery. Various techniques have been used to study specific proteins, including affinity chromatography, activity-based probes, affinity-based probes and photo-affinity labeling (PAL). PAL has become one of the most powerful strategies to study PPIs. Traditional photocrosslinkers are used in PAL, including benzophenone, aryl azide, and diazirine. Upon photoirradiation, these photocrosslinkers (Pls) generate highly reactive species that react with adjacent molecules, resulting in a direct covalent modification. This review introduces recent examples of chemical proteomics study using PAL for PPIs.
Keywords: CARBOHYDRATE-BINDING PROTEIN; SITE-SPECIFIC INCORPORATION; UNNATURAL AMINO-ACIDS; CELL-CULTURE SILAC; CROSS-LINKING; PHOTOAFFINITY PROBES; LIVING CELLS; IN-VIVO; ESCHERICHIA-COLI; GENETIC-CODE